Development and Standardisation of a Method for Inflicting Frostbite Injury in Rats and Formulation of Essential Oil in Treatment of Frostbite - Joshi, Kumud; Goyary, Danswrang; Mazumder, Bhaskar; Kishor, Sumit; Dey, Piyali; Bhutia, Yangchen Doma; Karmakar, Sanjeev; Chattopadhyay, Pronobesh; Dwivedi, Sanjai Kumar (Defence Life Science Journal, 2020)
Frostbite is a cold induced injury which occurs due to exposure of a particular site of body to sub-zero temperature. One of the primary reasons for lack of proper studies about the underlying mechanism of frostbite injury is due to non-availability of any reliable animal model and method for inflicting frostbite. In our current research, a device was designed and standardised to inflict frostbite wound in wistar rat. A formulation comprising different combination of essential oils was also developed and its activity was assessed and found effective in the treatment of frostbite wound.